Development of Flower Morphology E-Module Based on Tretes Waterfall Biodiversity to Improve Botanical Literacy And Communication Skills - Amalia Shaleha Putri; Sulisetijono Sulisetijono; Ibrohim Ibrohim (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Botanical literacy and communication skills are critical 21st-century competencies, yet they remain underdeveloped among Biology Education students. This study addresses this gap by developing and validating a flower morphology e-module that integrates local potential from the Raden Soerjo Natural Park. Methodology: Following the Lee & Owens development model, data were collected from 3 expert validators and students in one-to-one (n=3), small group (n=10), and field trials (n=32) using Likert scales, essay questions, and observation sheets. Findings: The e-module was rated "very valid" by experts (96.52% average) and "very practical" in student trials (86 - 89% average). A one-way ANCOVA test confirmed its effectiveness, showing a statistically significant and substantial increase in botanical literacy (80% average) and communication skills (78% average) in the experimental class over the control class. Contribution: This study contributes a validated and effective e-module that uniquely integrates local potential, offering a significant practical implication for the biology curriculum by providing educators with a resource to enhance student competencies through contextualized, self-directed learning